2017
DOI: 10.1093/police/pax011
|View full text |Cite
|
Sign up to set email alerts
|

Body-Worn Cameras and the Law of Unintended Consequences: Some Questions Arising from Emergent Practices

Abstract: Research on body-worn cameras (BWC) has tended, through evaluations or randomized controlled trials, to look to demonstrate some assumed benefit or consequence of the use of BWC. This article is concerned with the ways in which police officers use and talk about BWC and draw on ethnographic research over the past 30 months in one force as it rolled out the use of cameras. BWC have become a useful tool in the array of those available to officers. At the same time, they come with some downsides. There are pressu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
33
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 34 publications
(36 citation statements)
references
References 17 publications
2
33
0
Order By: Relevance
“…These mixed findings occur within both randomized controlled experiments as well as quasi-experimental research. In their ethnographic research, Rowe et al (2018) reported officers with BWCs feeling constrained in their discretion to not arrest, especially when there is evidence of an assault (i.e., they felt that had to carry out the arrest).…”
Section: Impact Of Bwcs On Arrest and Citation Behaviorsmentioning
confidence: 99%
“…These mixed findings occur within both randomized controlled experiments as well as quasi-experimental research. In their ethnographic research, Rowe et al (2018) reported officers with BWCs feeling constrained in their discretion to not arrest, especially when there is evidence of an assault (i.e., they felt that had to carry out the arrest).…”
Section: Impact Of Bwcs On Arrest and Citation Behaviorsmentioning
confidence: 99%
“…Furthermore, McClure et al (2017) and Peterson et al (2018) observed significant reductions in arrests for officers wearing cameras. The varied spectrum of inconsistent outcomes across trial contexts could be due, at least in part, to the interaction between BWV cameras and police discretion (Rowe et al 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Similar concerns have been raised in the policing literature, with some recognition that officer safety may be at risk if officers who are equipped with a BWC are hesitant to use force even in appropriate circumstances, due to the fear of being reprimanded for the inappropriate or excessive use of force (Rowe et al, 2017). This represents a concern if rather than increasing officer safety, BWCs, instead, endanger correctional officers who hesitate to use force against unruly individuals.…”
Section: Resultsmentioning
confidence: 84%